The effect of information technology on the agility of the supply chain in the Iranian power plant industry - Bargshady, G. (Emerald Group Publishing Ltd., 2016)
Purpose An agile supply chain (ASC) includes companies that are operationally linked to each other, such as supply, design, manufacturing and distribution centers that respond and react quickly and effectively to change markets. Information systems and technology have a main role in achieving this objective. Therefore, the purpose of this paper is to examine the relationship between information integration, information infrastructure flexibility and the ASC in the Iranian power plant industry (IPPI). Design/methodology/approach The quantitative method was employed in this study. Survey questionnaires were sent to 87 managers in the IPPI to examine the relationship between information integration, information infrastructure flexibility, and the ASC. Findings The final results indicated that information sharing and responsibility were strongly related with the ASC; accessibility and connectivity had important relations with the ASC; while the relationships between compatibility and adaptableness as IT flexibility variables and ASC were positive but not significant. Research limitations/implications This study focussed on the impact of IT on the IPPI specifically companies that manufacture boilers, electronic control tools, turbines, turbine blades, generators and other power plant-related components. Practical implications A new research model was developed to assess the impact of the interrelationships among IT capabilities and the ASC and results should assist managers as well as academicians. Originality/value An investigation was carried out through this study based on the current situation in IPPI to empirically examine and evaluate the effect of IT integration and flexibility on ASC. Besides, a very limited number of studies have been done on the implementation of information technology in the IPPI. Â© Emerald Group Publishing Limited.